Emulsion Polymerization Using Switchable Surfactants: A Route Towards Water Redispersable Latexes. Issue 1 (November 2013) - Su, Xin; Fowler, Candace; O'Neill, Catherine; Pinaud, Julien; Kowal, Erica; Jessop, Philip; Cunningham, Michael; Moritz, Hans‐Ulrich; Pauer, Werner
Summary Colloidal latexes of polystyrene and poly(methyl methacrylate) have been prepared by emulsion polymerization using amidine‐based switchable surfactants. Particles with sizes ranging from 50 nm to 350 nm were obtained. Destabilization of the latexes requires only air and heat which destabilize the latex by removing CO2 from the system. The resulting micron sized particles can be easily filtered to yield a dry polymer powder and a clear aqueous phase. We have also developed a new benign means of reversibly coagulating anionic latexes by using "switchable water", an aqueous solution of switchable ionic strength. The addition of CO2 and switchable water to an anionic latex can result in aggregation of the latex. Subsequent removal of CO2 by sparging with air allows the aggregated latex to be redispersed and recovered in its original state.